Terapia laser intrafetal para la secuencia perfusión arterial inversa en gemelos (TRAP). Comunicación de un caso y revisión de la literatura - Huertas Tacchino, Erasmo (2022)
A 41-year-old primigravida with double monochorionic biamniotic gestation, witha diagnosis of twin reverse arterial perfusion sequence (TRAP) and poor perinatalprognosis underwent intrafetal laser surgery at 18 weeks of gestation. It wascomplicated with premature rupture of membranes that was managed expectantlyuntil 33 weeks 3 days, when elective caesarean section was performed withoutcomplications. A healthy live newborn of 2,255 g was obtained and was dischargedfrom the hospital on the 15th day of birth without complications. We report the firstcase of intrafetal laser surgery performed in our country and highlight its efficacy,simplicity, low cost and ambulatory approach in cases of TRAP sequence.